Research on Hybrid Teaching Mode of Software Engineering Based on SPOC - Lei, Ma (Journal of physics. Conference series, 2019)
With the advent of the information age, the new teaching mode is emerging, and the traditional offline course and online teaching are constantly integrated and updated. By using SPOC teaching method, it is integrated into the course teaching of software engineering, and the study of hybrid teaching mode of software engineering based on SPOC can effectively improve the teaching quality of teachers and students' learning efficiency, and promote the cultivation of talents.